2023
DOI: 10.1021/acsami.2c20999
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Rich Ni–CoO@PEG Porous Hexagonal Nanosheets: Multi-enzyme and Ultrasound Catalysis for Synergistic Anticancer Treatment

Abstract: Given the similarity with photocatalysis, sonodynamic therapy (SDT) can be defined as ultrasonic (US) catalysis. Encouraged by the principles of photocatalysis and defect chemistry, defect-rich nickel (Ni)doped cobaltous oxide (Ni−CoO@PEG) porous hexagonal nanosheets have been synthesized as a sonosensitizer. The doping of Ni decreases the band gap that is testified by density functional theory to increase the US-generated charges. Under US irradiation, Ni−CoO@PEG nanosheets produce 1 O 2 as an active species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…These findings highlight the potential of ZIF-8 as a potent sonosensitizer in SDT, thereby contributing toward advancements in cancer treatment strategies. Oxygen vacancy or oxygen-deficient active centers D-MOF(Ti) MOF [46] M@C Cyan-coated Mn 1.4 WO x [47] DHMS MOF-derived Mn-based nanoparticles [48] Non-stoichiometric compounds TiH 1.924 Nanodots [49] TiO 1+x Ultrafine nanorod [50] MnWOx Ultrasmall bimetallic MnWOx nanoparticles [51] Defects-rich structure H-Ti 3 C 2 MXenes [53] TiO 2 @TiO 2-x Metal oxides [54] Bi-HJ Metal oxides [55] TiN Ultrasmall nanodots [56] Ni-CoO @PEG Metal oxides [57] Heterojunction-inhibited electron-hole pair recombination MIL@Ag Silver-MOF [61] TiO 𝛼-Fe 2 O 3 @Pt Metal-metal oxides [71] N-CD@LiFePO 4 Carbon dots-metal oxides [72] Au−rGO−ZnO Metal-graphene oxide-metal oxides [73] Acoustic radiation force-induced piezoelectricity catalysis for charge separation P-BTO ultrasmall tetragonal nanoparticles [76] T-BTO non-centrosymmetric tetragonal nanocrystals [77] MnTiO 3 Metal oxides nanodisk [78] MP-Au/ZnO@CCM non-centrosymmetric crystal [81] UIO-66-Au Au-MOF [86] MT-MOF TNS Bi-metal-MOF [87] Sonocatalytic topology structure inheriting carbon nanospheres MOF-derived carbon nanospheres [89] FePc NDs MOF-derived metal nanodots [90] Table 2. A summary advantages and disadvantages of various design concepts.…”
Section: Charge Transfer Enhancementmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings highlight the potential of ZIF-8 as a potent sonosensitizer in SDT, thereby contributing toward advancements in cancer treatment strategies. Oxygen vacancy or oxygen-deficient active centers D-MOF(Ti) MOF [46] M@C Cyan-coated Mn 1.4 WO x [47] DHMS MOF-derived Mn-based nanoparticles [48] Non-stoichiometric compounds TiH 1.924 Nanodots [49] TiO 1+x Ultrafine nanorod [50] MnWOx Ultrasmall bimetallic MnWOx nanoparticles [51] Defects-rich structure H-Ti 3 C 2 MXenes [53] TiO 2 @TiO 2-x Metal oxides [54] Bi-HJ Metal oxides [55] TiN Ultrasmall nanodots [56] Ni-CoO @PEG Metal oxides [57] Heterojunction-inhibited electron-hole pair recombination MIL@Ag Silver-MOF [61] TiO 𝛼-Fe 2 O 3 @Pt Metal-metal oxides [71] N-CD@LiFePO 4 Carbon dots-metal oxides [72] Au−rGO−ZnO Metal-graphene oxide-metal oxides [73] Acoustic radiation force-induced piezoelectricity catalysis for charge separation P-BTO ultrasmall tetragonal nanoparticles [76] T-BTO non-centrosymmetric tetragonal nanocrystals [77] MnTiO 3 Metal oxides nanodisk [78] MP-Au/ZnO@CCM non-centrosymmetric crystal [81] UIO-66-Au Au-MOF [86] MT-MOF TNS Bi-metal-MOF [87] Sonocatalytic topology structure inheriting carbon nanospheres MOF-derived carbon nanospheres [89] FePc NDs MOF-derived metal nanodots [90] Table 2. A summary advantages and disadvantages of various design concepts.…”
Section: Charge Transfer Enhancementmentioning
confidence: 99%
“…In terms of element doping, Wang et al synthesized defectrich nickel (Ni)doped cobaltous oxide (Ni-CoO @PEG) porous hexagonal nanosheets as a sonosensitizer. [57] The doping of Ni led to a decrease in the bandgap, resulting in an increase in the ). Reproduced permission from reference.…”
Section: Defects-rich Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Nanozymes are materials that have functions similar to natural enzymes . Due to their excellent stability, easy large-scale preparation, and tunable chemical or physical properties, they are widely used in the field of biosensing. However, the inherent complex structure of common nanozyme materials hinders the in-depth understanding of the catalytic properties of nanozymes, which creates obstacles for the directional design of nanozymes according to functional requirements. Among various types of nanozymes, single-atom nanozymes (SANs) have received more attention due to their unique well-defined geometric and electronic structures, maximum atom utilization, abundant active sites, and unique quantum size effects. In terms of the construction of the detection platform, SANs are more suitable for the development of small sensor parts with the advantages of low cost, high stability, and well-designed orientation function. , At present, the methods of synthesizing SANs include MOF derivatization method, wet chemical strategy, atomic deposition strategy, and so on. , Xu et al reported the synthesis of a Zn–N 4 SAN with a metal content of 3.12 wt % by pyrolysis of ZIF-8 .…”
Section: Introductionmentioning
confidence: 99%
“…[22] With the advantage of produced abundant oxygen vacancies (O V ), the efficient separation of electron-hole pair lower resistance for charge transfer after the doping of Ni, Wang et al prepared NiÀ CoO nanosheets exhibited an better glucose oxidase activity. [23] Lu designed and synthesized a novel and stable Pt nanocluster doped CoO (Pt/CoO) for sensing of nitrite, which displayed high sensitivities of 408.5 μA mM À 1 cm À 2 as well as a low detection limit of 0.067 μM because of the strongmetal support interaction (SMSIs) can greatly enhance the electrocatalytic activity of Pt/metal oxide. [24] On the other hand, the additional binders used for coating the catalyst on electrode also usually lead to reduced charge transfer rate, decreased cycle time and material denaturation as a result of the formation of "dead volume".…”
Section: Introductionmentioning
confidence: 99%